ANALISIS DELIBERATIF TERHADAP IMPLEMENTASI KEBIJAKAN ALOKASI DANA PEMBANGUNAN SARANA DAN PRASARANA WILAYAH DI KECAMATAN PEDURUNGAN, KOTA SEMARANG - Fibrianingsih, Vita Dwi Nur; Subowo, Ari; Santoso, R Slamet (Journal of Public Policy and Management Review, 2015)
Fund allocation policy infrastructure development in the area of Semarang in line with one of the principles of poverty reduction is to improve poor people's access to basic services. Only in District Pedurungan experiencing poverty increased amount while the allocation of development funds to increase. The purpose of this study was to analyze the contents of deliberative policy (content of policy) and implementation environment (context of impelementation) policy of allocation of funds for development of infrastructure in Sub Pedurungan region. The method used is deliberative analysis method that uses the concept of good governance as an analytical tool. Results from this study indicate that the deliberative analysis of the nine parameters that have the greatest correlation is the principle of participation. For most indicators correlated with the principle of deliberative analysis is the location of the decision-making correlates with the principles of participation, rule of law, transparency, and accountability. While the deliberative analysis parameters that correlate to the environment fund allocation policy implementation infrastructure development in the district region Pedurungan, Semarang City, among others, the rule of law, responsivenessÂ¸dan strategic vision. Of the three parameters most correlated is the principle of responsiveness. For most indicators correlated with the principle of deliberative analysis is compliance and implementing responses were correlated with the principle of rule of law and responsiveness. The conclusion from this study is that there are three factors on the content of the policy with criteria of deliberative analysis of their implementation is still weak participation on the type of benefit, transparency and accountability on the location of decision making, as well as resources with criteria of transparency and efficiency. Recommendations are given is intensifying LPMK to improve supervision and for the price standardization efforts to ensure the efficiency of development.